A sustentabilidade e a ação coletiva que contribuem para a Indicação Geográfica do mel - Indicação de Procedência Oeste do Paraná - Durso, Emerson Di Domenico (2018)
Local products, recognized as Geographical Indications, are strongly related to the nature, the people, the culture and traditions. From such perspective, they show up as tools to promote the sustainability of the regions where products are made and as an alternative to differentiate and promote local products. This work has been motivated by the studying economic, environmental and social dimensions of sustainability in the development of the collective strategy underway in beekeeping in the western region of Paraná, especially by its contribution to the consolidation of the Geographical Indication. In the case under study, the Geographical Indication was recognized in July 2017 as Indication of West of Paraná product. Coofamel is the representative entity of Apis Africanizada and Jatái bee honey producers from that region. For this purpose, questionnaires were applied to the president of Coofamel and to representatives of partner institutions. These surveys in the field aimed to know the support of partners and beekeepers for the sustainability of the Geographical Indication. Also from a questionnaire, information about the cooperative member's perception about the influence of the cooperative on the dimensions of sustainability and collective actions has been raised. As a main result, a significant support from the regional entities in the promotion of agriculture with low environmental impact has been identified. Along with the supporting entities, beekeepers promote actions to recover degraded areas, by planting native plants, conserving natural resources and biodiversity, among other actions. It has also been noticed that the contribution of the partners and the union of beekeepers made it possible to build and adapt beneficiation structures, to qualify production in the field and in the processing, as well access to the marketplace and to innovation, essential factors for the economic sustainability of the collective initiative. The results showed that the collective action established in beekeeping in the West of Paraná provided greater involvement of the family of producers with the activity and in the promotion of community quality of life. Honey producers in the region have made partnerships with other producer associations, establishing interaction and socialization with actors not only in beekeeping, but in other activities as well. The strengthening of associativism allowed the exchange of information among beekeepers to improve the honey production process. The trainings promoted by the partner entities enabled beekeepers to escape from clandestine commercialization and to offer a safe product for their own consumption and for the marketplace. Thus, collective action has also contributed to the social dimension of sustainability. In view of the above, it is concluded that the strong institutional support contributes strongly to the sustainability and consolidation of the Geographical Indication. However, there was a trend in the increase in the number of cooperative members and the presence of “associated riders”, those who only want to take advantage of the collective effort without making any contribution. Among the recommendations, the attention has been given to Coofamel´s communication with its members in order to ensure the consolidation of the Geographical Indication